Gambaran Pelaksanaan Discharge Planning Pada Pasien Diabetes Mellitus - Haryono, Rudi; Effendy, Christantie; Aulawi, Khudazi (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2008)
Please refer to the file